Fatal Frost - Mehl, Nancy (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2016)
"Mercy Brennan followed in her father's footsteps in a law enforcement career, but she has no interest in any other connection to him. A U.S. Marshal in St. Louis, Missouri, she's assigned to a joint task force with the St. Louis PD that puts her back into contact with her father and in the sights of St. Louis's most powerful gang. When the gang has reason to believe Mercy has possession of some highly sensitive and incriminating information, her boss assigns Mark St. Laurent--a Deputy U.S. Marshal and Mercy's ex-boyfriend--to get her out of town until they can guarantee her safety"--Amazon.com.
Keywords: United States marshals -- Fiction; Gangs -- Fiction; Fathers and daughters -- Fiction; Saint Louis (Mo.) -- Fiction; Detective and mystery fiction; Christian fiction